The Effect of Strategic Foresight on Competitiveness, with the Mediating Role of Strategic Learning (Case Study: Private Banks of Kermanshah City) - Eskandari, Faranak; Dr. Esfandyar Mohammadi,; Hamzeh Rahimi, (Technium Social Sciences Journal, 2020)
The purpose of this paper was to investigate the impact of strategic foresight on competitiveness by moderating the role of strategic learning in Kermanshah private banks. The present study was a quantitative one and was applied in terms of purpose and nature of the descriptive-correlational method and The questionnaire was distributed in two ways; the library and the field .For validity of the research questionnaire, face validity and expert opinion of instructors and consultants were used and for reliability of the questionnaire Cronbach's alpha coefficient and test performance test were used. There are 208 individuals in the city of Kermanshah with a sample of 135 people selected through our random sample using Morgan table. Data analysis was performed using descriptive and inferential statistics.